Optimisation of high bar circling technique for consistent performance of a triple piked somersault dismount - Hiley, M. J.; Yeadon, M. R. (Journal of Biomechanics, 2008)
The dismount from the high bar is one of the most spectacular skills performed in Men's Artistic Gymnastics. Hiley and Yeadon [2005]. Maximal dismounts from high bar. Journal of Biomechanics 38, 2221-2227] optimised the technique in the backward giant circle prior to release using a computer simulation model to show that a gymnast could generate sufficient linear and angular momentum to perform a triple piked backward somersault dismount with a sufficiently large release window (the period of time during which the gymnast could release the bar and successfully complete the dismount).